Distracted by "distracted pedestrians"?. (May 2020) - Ralph, Kelcie; Girardeau, Ian
Abstract: Some observers view distracted walking as a menace, while others contend that concern is overblown. Understanding these competing frames about pedestrian safety is essential because interpretive frames influence how we try to solve problems. In this study, we survey transportation practitioners to gauge how concerned they are about distracted walking, assess whether windshield bias and professional training influence concern, and determine whether concern influences preferred policy solutions for reducing pedestrian deaths. One third of transportation practitioners surveyed view distracted walking as a large problem, estimating that it was responsible for 40% of pedestrian deaths. Practitioners were more concerned about distracted walking if they primarily use a car or spend little time in pedestrian -oriented areas (windshield bias), or if they work in engineering or public health (professional training). Most importantly, the distracted walking frame does indeed shape policy solutions. Practitioners concerned about distracted walking were more likely to endorse individual-level solutions (like educational campaigns) and were less likely support reducing vehicle speeds. Concern about distracted walking detracts attention from more deadly risk factors, more effective policy approaches, and, most importantly, is inconsistent with the ethos of making streets safe for all users, including children, the elderly, and vision impaired people. Instead of focusing on educational campaigns, practitioners should focus their pedestrian safety efforts on the biggest risk factors and the most effective solutions. Highlights: A third of transportation practitioners say distracted walking is a big problem Half say it is a small problem and 17% say it is not a problem Concern is highest among drivers and those who spend little time in pedestrian areas Concern is higher among engineers and public health practitioners than planners Concern affects policy solutions, raising support for education over speed reduction